Climate change innovation: Does board gender diversity matter? - Isabel-María García-Sánchez; Sónia Maria da Silva Monteiro; Juan Ramón Pi\~neiro Chousa; Beatriz Aibar-Guzmán (Journal of Innovation & Knowledge (JIK), 2023)
This paper responds to recent calls to study the role that board gender diversity plays in shaping corporate responses to climate change. It examines whether female board representation is associated with greater climate change innovation and whether its effect is determined by the presence of a greater number of independent female directors or the existence of a critical mass of female directors. The results obtained for a panel data of 3,928 companies over the period 2010-2020 (35,199 observations) confirm that companies with a greater female board representation (both in number and in percentage) are more proactive in terms of investments in climate change innovation. This positive effect does not require a critical mass of female directors and diminishes when the percentage of female directors is higher than 46.78%, a proportion associated with the presence of five or more female directors. Furthermore, female directors influence climate change innovation mainly through their involvement in management as executive directors, rather than through the monitoring and advisory roles that characterize independent directors. The theoretical and practical implications derived from this research are robust to different considerations and methodological approaches.
Keywords: M14; O44; Q01; Q54; 650; Board gender diversity; Climate change; Corporate governance; Critical mass; Environmental innovation; Human capital